PENGARUH STRUKTUR MODAL DAN KEPEMILIKAN KELUARGA TERHADAP KINERJA SAHAM DENGAN PROFITABILITAS SEBAGAI PEMEDIASI - Parintak, Sutrisno; Amiruddiin; Rasyid, Syarifuddin; Darmawati (Jurnal Akuntansi Trisakti, 2024)
This study aims to examine the effect of capital structure and family ownership on stock performance with profitability as a moderating variable. The sampling technique used purposive sampling method. Sampling using this technique resulted in a sample of 72 manufacturing companies listed on the Indonesia Stock Exchange (IDX). Research data testing using multiple regression techniques. The test results show that capital structure and family ownership have a significant positive effect on profitability. The test results also show that profitability is able to mediate the effect of capital structure and family ownership on stock performzance.